Family Empowerment for Pressure Ulcer Prevention in Bedridden Patients at Home in Bababulo Village - Hasifah, Hasifah; Jamaluddin, Maryam; Alawiyah, Tuty; Kasim, Jamila; Setiawati, Yuliyanti (Room of Civil Society Development, 2025)
Pressure ulcers are a common and serious health problem among bedridden patients receiving home care, often leading to complications that deteriorate their condition. This community service program aimed to empower families as primary caregivers in preventing pressure ulcers through structured education and practical mentoring. The intervention involved 30 family caregivers and was implemented in two sessions consisting of education and hands-on practice, conducted on May 10, 2025, in Bababulo Village, Pamboang District. Knowledge evaluation was performed using a pre-test and post-test design with 15 structured questions. The results showed a substantial improvement in family knowledge, with the average score increasing from 48.3 to 89.5 after the intervention. Participants initially demonstrated limited understanding of ulcer prevention techniques but became more competent and confident following the sessions. The program not only improved knowledge and caregiving skills but also strengthened emotional engagement and collaboration within families. Despite its success, the short training duration and small sample size were identified as limitations. To ensure sustainability, it is recommended to integrate digital educational materials, continuous follow-up training, and community support networks. Overall, this initiative provides an effective and replicable model for family-based empowerment in home care, contributing to enhanced patient safety and quality of life.